2006
DOI: 10.1109/tbme.2006.870257
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Fibrillation Potentials—a New Analytical Description for the Muscle Intracellular Action Potential

Abstract: The single-fiber action potential (SFAP) can be modeled as a convolution of a biolectrical source (the excitation) and a transfer function, representing the electrical volume conduction. In the Dimitrov-Dimitrova (D-D) convolutional model, the first temporal derivative of the intracellular action potential (IAP) is used as the source. In this model, the ratio between the amplitudes of the second and first phases of the SFAP (which we call the PPR, after peak-to-peak ratio) increases invariably with radial dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 15 publications
5
34
0
Order By: Relevance
“…Second, in both diagrams most lines lie within an area limited by a lower-PPR limit of 0.5 and an upper-PPR limit of 1.5. This result is in good agreement with previous reports for potentials recorded using a single fibre electrode (Rodriguez et al, 2006(Rodriguez et al, , 2009. Finally, note that most lines with a steep gradient (over 0.4 or under À0.4) include PPR values either greater than 1.5 or lower than 0.5.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Second, in both diagrams most lines lie within an area limited by a lower-PPR limit of 0.5 and an upper-PPR limit of 1.5. This result is in good agreement with previous reports for potentials recorded using a single fibre electrode (Rodriguez et al, 2006(Rodriguez et al, , 2009. Finally, note that most lines with a steep gradient (over 0.4 or under À0.4) include PPR values either greater than 1.5 or lower than 0.5.…”
Section: Resultssupporting
confidence: 94%
“…1(b)) (Dimitrov and Dimitrova, 1974;Miller-Larsson, 1985). The concept of the peak-to-peak ratio (PPR) of a SFAP, defined as the absolute value of the quotient of V 2 over V 1 , was introduced by the current authors in 2006 (Rodriguez et al, 2006) but at that time was only studied in a small collection of fibrillation potentials. Our preliminary studies were extended in a recent work (Rodriguez et al, 2009) in which we recorded a large number of SFAPs from the right tibialis anterior muscle of four normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present work suggest that we should admit some variability in the duration of the IAP depolarization portion in order to be able to generate the range of risetimes observed experimentally. This proposal is in agreement with several other studies that have demonstrated that to explain the changes of certain SFAP parameters it is necessary to consider the excitation source as a variable function (Rodriguez et al, 2006(Rodriguez et al, , 2007(Rodriguez et al, , 2009(Rodriguez et al, , 2010.…”
Section: Considerations For Future Sfap and Mup Modelingsupporting
confidence: 91%
“…The second, third and fourth IAP phases model the repolarization process occurring at the membrane of the cell after the depolarization. The duration of this repolarization portion is controlled by parameter T spl (Dimitrov and Dimitrova, 1998;Rodriguez et al, 2006). We shall refer to A 1 , A 2 , A 3 and T spl as excitation parameters.…”
Section: Dimitrov-dimitrova (D-d) Sfap Convolutional Modelmentioning
confidence: 99%
See 1 more Smart Citation